Setting a Nigeria national malaria operational research agenda: the process - Olufemi Ajumobi; Perpetua Uhomoibhi; Pamela Onyiah; Obafemi Babalola; Salami Sharafadeen; Maduka D. Ughasoro; Al-Mukhtar Y. Adamu; Oluwaseun Odeyinka; Taiwo Orimogunje; Ibrahim Maikore; Emmanuel Shekarau; Akintayo Ogunwale; et al. (BMC, 2018)
Abstract Background Employing malaria operational research (MOR) findings in planning national malaria control programmes is gaining increased attention. The malaria control foci are diverse, resources are limited; therefore, agreeing on priority areas is critical. Hitherto, the process of prioritising MOR questions in Nigeria has been limited to few stakeholders. In support of the National Malaria Elimination Programme's (NMEP) effort at setting a MOR agenda, the Nigeria Field Epidemiology and Laboratory Training Programme (NFELTP) in collaboration with NMEP conducted preliminary exploratory study to identify key malaria research gaps and needs, and provide data to inform setting a robust national MOR agenda. The process of generating data is presented in this paper. Methods A twelve-member task-team comprising NFELTP, university researchers and NMEP officers was commissioned. Following an inaugural meeting the task-team developed a framework of activities and held five planning meetings, conducted five-week online and self-administered paper-based surveys, key informant interview (KII), two-day desk review workshop, seven-day qualitative data analysis, ten-day result and five-day report writing workshops. Paired group members conducted the interviews across six geopolitical zones of Nigeria. Abridged study report was used for a two-day MOR setting agenda stakeholders' workshop. Results A structured framework, study protocol and data collection instruments were developed and submitted for ethical approval. The instruments included survey questionnaire for detailed information on researchers and other stakeholders' experience with MOR, the gaps and needs in thematic MOR areas; KII and Delphi guides. After an initial scoping review, primary data were collected from purposively selected survey participants using mixed methods: - online survey (n = 100), self-administered paper-based survey (n = 85), KII (n = 40), desk review workshop (n = 22) and Delphi interviews (n = 8). Comprehensive lists of research gaps/bottlenecks and needs were generated for each thematic area in malaria control. These were used at a two-day national MOR setting stakeholder workshop (n = 54) to guide the development of national MOR agenda document. Conclusions A systematic approach involving broad stakeholder engagement provided data and evidence-based information for development of a robust national MOR agenda. The processes involved are recommended for use in malaria endemic settings.